Ki-67 expression as a diagnostic biomarker in odontogenic cysts and tumors: A systematic review and meta-analysis - Mahnaz Jabbarzadeh; Michael R. Hamblin; Fatemeh Pournaghi-Azar; Maedeh Vakili Saatloo; Maryam Kouhsoltani; Nafiseh Vahed (Tabriz University of Medical Sciences, 2021)
Ki-67 is a marker of cell proliferation, used as an important diagnostic marker in the pathologic differentiation of various lesions. It is also relevant for developing targeted molecular therapies. We carried out a systematic review to assess the Ki-67 labeling index (LI) in odontogenic cysts and tumors. Databases were searched, including PubMed (MEDLINE), Scopus, CINHAL, PsycoInfo, the Cochrane Library, and Proquest. The meta-analysis was carried out based on the data of 608 lesions. When a 5% cut-off point was set, ki-67 LI of all benign odontogenic tumors dropped below this point. All the malignant tumors demonstrated an LI of over 15.3%; a significantly higher Ki-67 LI in malignant odontogenic lesions (17.59±2.80) was observed. Among benign tumors, the largest and the smallest Ki-67 LIs were seen in ameloblastoma (4.39±0.47) and adenomatoid odontogenic tumor (0.91±1.71). The mean values of Ki-67 LI in tumors and cysts were 4.23 (0.38) and 1.04 (0.07), respectively. Among odontogenic cysts, the highest Ki-67 LI was found in odontogenic keratocyst (OKC) (3.58±0.51), and the lowest in the radicular cyst (1.29±0.62%). Ki-67 LIs in all odontogenic cysts were <3%, except for OKC. This controversial lesion seems to have a profile more similar to a tumor, and a treatment plan similar to tumors might be suggested. We found that odontogenic lesions have diverse proliferative activities that help differentiate between various lesions and suggest therapeutic plans.